Phytochemical Analysis, Anti-Microbial and Anti-Tuberculosis Activities of Methanol Extract of Piliostigma Thonnigii Leaves Extract - Malgwi, Daniel W.; Zarto, Saleem Sule; Adamu, Rakiya D.; Dowell, Farimani B. (Darul Yasin Al Sys, 2024)
The purpose of this study is to evaluate the antibacterial, anti-tuberculosis, and phytochemical screening properties of a crude extract of P. thoningii leaves from the Girei local government area in Adamawa state, Nigeria. Standard procedures were used for phytochemical screening, and the disc diffusion method was used for evaluations of antibacterial sensitivity and anti-tuberculosis activity. When leaves extract was screened phytochemically, alkaloids, flavonoids, phenol, terpenoid, quinone, and resins were found, but tannin and saponins were not. The greatest concentration of 500 ug/ml was used to evaluate the antibacterial activity against various pathogens. The results indicated that the zone of inhibition for E. Coli was 19 mm, for Staphyloccocus aureu it was 17 mm, for Salmonella typhi it was 20 mm, for Klabsiella pneumonia it was 26 mm, and for pseudomonas it was 22 mm. With a positive control of streptomycine, 30 ug at 28 mm inhibitory zone, anti-tuberculosis activity shown that the bacteria growth was suppressed at different concentrations of 500 ug/ml (12 mm), 250 ug/ml (9 mm), 125 ug/ml (8 mm), and 6.25 ug/ml (7 mm) growth. This study highlights the P. thoningii plant's potential as a source for the development of anti-tuberculosis (TB) drugs.